THE EFFECTIVENESS OF USING INSTAGRAM IN DEVELOPING STUDENTS’ DESCRIPTIVE TEXT WRITING - Ari Hilman (JALL (Journal of Applied Linguistics and Literacy), 2019)
ABSTRACTThis study investigates the effects of Instagram on students’ descriptive text writing of Islamic Senior High School students as well as to find out their perceptions of using Instagram for learning descriptive text writing. In doing so, the subjects consisted of 48 students who were in tenth grade. Then they were divided into two equal experimental and control groups (N=24).Their age ranged between 16 and 17 years old. Gender of participants was not considered as a variable in the study. This study used convergent parallel mixed-method whereas pre-test and post-test were administrated to collect quantitative data and questionnaire was given to collect qualitative data. The experimental group was taught descriptive text writing via Instagram application, whereas the control group followed Facebook application. Analyzing the data through the independent sample t-test revealed that with the help of Instagram application, the experimental group outperformed the control group in terms of writing descriptive text. Furthermore, Islamic Senior High School students had a positive attitude toward utilization of Instagram application.Keywords: Instagram, students, descriptive text writing